Oxidation of Aspirin by N-Sodio-N-Bromobenzene Sulphonamide (Bromamine-B) in Acid Medium; A Kinetic and Mechanistic Study - Ananda, S.; Ramananda, M.G.; Jagadeesha, M.B.; Puttaswamy (Asian Journal of Chemistry, 2010)
The kinetics of the oxidation of aspirin (ASP) by bromamine-B (BAB) has been studied in aqueous perchloric acid at 303 K. Decarboxylation, bromination and loss of acetic acid gave the reaction product 2,4,6-tribromophenol and was identified by GC-MS. The rate shows first order dependence on [BAB], fractional order in [ASP] and inverse fractional order in [H+]. The rate decreased with decreasing dielectric constant of the medium. The variation of ionic strength and the addition of the reaction product (benzene sulphonamide) and halide ions had no significant effect on the reaction rate. Thermodynamic parameters were evaluated. The solvent isotope effect was studied using D2O.